Case Report: Congenitally Missing Teeth - Fatemeh Jahanimoghadam; Moolok Torabi; Shima Rostami (Anatomical Sciences Journal, 2015)
Congenitally missing of maxillary lateral incisors is one of the most common patterns of hypodontia. This paper presents a nine year old boy with congenital missing of lateral incisors. Familial history showed that, his mother, aunts, uncle and grandmother have also congenital absence of lateral incisors.